THE RELATION OF COLD SURGE PROPAGATION WITH EQUATORIAL WAVES - Ayu Lestari, Tri
Cold Surge (CS) is a southward meridional air-mass flaw from extratropical to tropical and equatorial region. A previous study shows that there are three pathways for CS propagation into the tropics i.e., CS passing through the South China Sea (CS-SCS), the Philippine Sea (CS-PHS), and both regions (CS-Both). Theformation of thispathways is thought to be related to easterly wave activities, but the modes of these waves and haw they affect the CSpathways are still elusive. In this study, the signatures of easterly waves are examined using Space-Time Spectral Analysis (STSA) in terms of Equatorial Rossby (ER) and Mixed Rossby Gravity (MRG) waves. The STSA analysis is applied to Outgoing Longwave Radiation (OLR) data of 40 winters from 1979180 to 2018119. Additionally, reanalysis data are also used to analyze the spatial wave patterns in the wind and pressure fields. The resulted space-time spectra shaw an enhancement in ER and MRG wave activity during the CS-SCS and CS-PHS events. The spatial correlations betweenfiltered and raw OLR data confirm that thepresence of ER waves can be associated with at least 50% of the analyzed CS-SCS and CS-PHS events. The signatures of the ER wave mode are mainlyfound in the wavenumbers of -4 to -3, and periods of 16 to 48 days. Further analysis on the local phase of the waves indicate that ER waves may affect the CS pathways by controlling the location synoptic-scale pressure and the associated vorticity field anomalies prior or concurrent to the arrival of CS into the tropics.